Job satisfaction of librarians in the federal university libraries in Nigeria - Lawal, Akanbi Mohammed (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
Job satisfaction can be described as the combination of the emotional and behavioral attitude of an individual towards the job he/she performs. The psychologists, and behaviorists as well as librarians have stressed the importance of motivation and the role of behavior of workers in relation to the satisfaction derived from the job they performed. It is a well-known fact that a happy worker would be a more productive worker and a job satisfied worker would be a happy worker. On the contrary, the economic recession, which began in the early 1980's in Nigeria, had adverse effects on various job sectors which did not exclude the library profession, and this has resulted in setbacks particularly in terms of acquisition of resources, personnel and appropriate budgets for libraries. The result of this socio-economic imbalance was the absence of essential ingredients for satisfaction at work. Consequently, the librarians developed poor attitude towards their works, thereby resulting in low output. This study examines the job satisfaction of librarians in the Federal University Libraries in Nigeria with a view to determining their level of satisfaction through their attitudes towards Condition of Service, Work Environment, Faculty Status and Unionism. Survey research method is employed as a technique for this study. The population of study comprised of all the librarians in federal university libraries in Nigeria with at least a Bachelor of Library and Information Science (BLIS) degree. Stratified random sampling technique was adopted for this study. Questionnaire and interview were used as instruments for data collection and analysis. The findings showed that there was no significant difference in the level of job satisfaction of librarians in Nigerian Federal University Libraries, indicating that there is high level of job satisfaction among the librarians in Nigerian Federal University Libraries. There was a strong positive relationship between job satisfaction of librarians and Work Environment, but a relatively weak correlation between job satisfaction of librarians and Condition of Service. There was negative correlation between job satisfaction and Unionism, but no relationship at all between job satisfaction of librarians and Faculty Status. The findings also showed a significant difference between job satisfactions of librarians in Federal University Libraries in Nigeria and the following Demographic Variables such as Salary Grade, Rank, Length of Service and Annual Income, but no significant difference with Highest Qualification, Length of Service, Gender, Marital Status and Age of the librarians. The Federal Government, University Authorities and Library Management need to assist in enhancing and maximizing job satisfaction of librarians through Condition of Service, Faculty Status and Unionism for better information services to the academic communities and beyond.